Study of Leachate and Waste Composition at Different Landfill Sites of Nepal - Adhikari, B.; Manandhar, D.R.; Khanal, S.N. (Kathmandu University Journal of Science, Engineering and Technology, 2013)
The study focuses on waste composition and leachate characteristics at different landfill sites in Nepal, namely Sisdole (Kathmandu), Pokhara, and Karaute Dada (Dang). Waste composition was analyzed onsite, and leachate samples were collected for analysis. Results showed high organic content in waste at all sites, with percentages of 61.6%, 52.5%, and 65% at Sisdole, Pokhara, and Karaute Dada, respectively. The age of the landfill and waste composition significantly influenced leachate composition, with fresh leachate containing higher levels of BOD5 and CODcr. Landfills with a higher percentage of organic content exhibited elevated BOD5 and CODcr values.